AIE-active florescent polymers: The design, synthesis and the cell imaging application. (20th December 2017) - Lei, Lei; Ma, Hengchang; Qin, Yanfang; Yang, Manyi; Ma, Yucheng; Wang, Tao; Yang, Yuan; Lei, Ziqiang; Lu, Dedai; Guan, Xiaolin
Abstract: Fluorescence imaging, especially specific organelle imaging, has become a significant technology to comprehending cell transplantation, migration, division, fusion, and lysis. In this paper, we designed and synthesized a water soluble and fluorescent polymer named as Poly(AA-TPA-d), which was pH-responsive by the fluorescence channel due to the presence of poly acrylic acid as the polymer backbone. The research results demonstrated that Poly(AA-TPA-d) exhibits novel aggregation-induced-emission (AIE) property. Additionally, due to the hydrogen bond formation and C=O···π interactions between methyl acrylate groups, Poly(AA-TPA-d) was of excellent hydrogel formation ability. Moreover, Poly(AA-TPA-d) displayed good bio-compatibility with the living MPC5 cells and highly specific cytoplasm-targeting ability by MTT assay and cell staining experiment respectively. Graphical abstract: Highlights: Combiningthe pH-responsive PAA with AIE active TPA derivative successfully. pH-responsive property. A cytoplasm imaging.